Evaluation of newborn hearing screening program in Jordan - Obeidat, Faten S.; Alothman, Noura; Alkahtani, Rania; Al-Najjar, Sameer; Obeidat, Mohammad; Ali, Asia Y.; Ahmad, Elham; Alghwiri, Alia A. (Frontiers in Pediatrics, 2024)
The Newborn Hearing Screening (NHS) program was officially launched in Jordan in 2021. Since its inception, no studies have examined the effectiveness of the program. This study seeks to assess the effectiveness and outcomes of the NHS program in Jordan. A retrospective cross-sectional study was conducted to investigate the program coverage rate, referral rate, loss to follow-up rate and the hearing status of newborns who successfully completed the necessary diagnostic assessment. Live births in all hospitals administered by the Ministry of Health (MoH) in Jordan from July 2021 to November 2023 were included.Out of 25,825 newborns delivered, 99.4% (25,682) were screened. A referral rate of 0.7% (189) was recorded.Approximately 61.9% of those referred (n=117) had normal hearing, while 31.7% (60 infants) were diagnosed with hearing loss. The prevalence of congenital hearing loss was 0.14%, and the mean age for identifying hearing loss was 11 months. The current status of the NHS program in Jordan is promising. The program has achieved most benchmarks recommended by the Joint Committee on Infant Hearing (JCIH), demonstrating encouraging outcomes. There is a need to investigate and address the factors causing delays in the identification of hearing loss in Jordan.